Efeitos da elevada concentração de sódio no fenótipo migratório de células endoteliais - Torres, Bianca Magnago (2017)
Endothelial cell (EC) migration plays a central role in vascular response to pathological processes involved in vascular remodeling and formation of new vessels. High sodium (HS) is associated with cardiovascular disease and endothelial dysfunction. Although there are already studies showing changes in the endothelium when exposed to HS, it is important to understand how it may impact migratory phenotype of EC and the underlying molecular mechanisms. OBJECTIVE: To test the hypothesis that HS affects migratory phenotype of EC and investigate mechanisms involved independently of hemodynamic factors. METHODS: Human umbilical vein lineage of endothelial cell (EA.hy926) was used. Cell migration was evaluated by Wound-Healing method in the conditions: High sodium (HS, NaCl:160mM) and Control, (CT, NaCl:140mM) and with Candesartan, DPI, Tiron and Allopurinol blockers (N = 5 to 7). Superoxide anion production (O2-) was evaluated by DHE. O2- generated by NADPH oxidase activity was determined by chemiluminescence assay. Expression of adhesion molecules associated with migration was analyzed by RT-PCR. Shear Stress was performed using a rhythmic shake that mimics the shear. RESULTS: Migration was evaluated every two hours in period of 10h. HS reduced EC migration compared to CT (CT, 100 ± 14% vs HS, 74 ± 5%, p <0.05) and Candesartan prevented these findings (* HS + Candesartan, 95 ± 7%), a similar result was seen with NADPH oxidase (* HS + DPI, 101 ± 12%) (* vs. HS, p<0.05). NADPH oxidase activity was increased when EC were exposed to HS and it was reduced by its inhibitor and AT1 receptor blocker (CT, 100 ± 24% vs HS, 375 ± 7%; HS + Candesartan, 116 ± 7%, HS + DPI, 110 ± 22%, * vs HS, p <0.05). HS incubation leads to an increase in O2 - production which was also inhibited by blocking the same pathways (CT, 100 ± 3% vs HS, 472 ± 15%, p <0.05). HS decreased adhesion molecules expression via NADPH oxidase (Integrin Alpha 5, Integrin Beta 1, Integrin Beta 3, VE-Cadherin and PECAM) and partially via AT1 receptor. In addition, HS decreased nitrite production through shear stress and Candesartan and DPI prevented this response (CT: 100 ± 9%, SS: 503 ± 20%, HS: 69 ± 10%, HS + SS: 134 ± 21%). SS + Candesartan: 477 ± 19%, SS + DPI: 498 ± 19%). CONCLUSION: This study demonstrated that HS reduces EC migration by reducing adhesion molecules expression via AT1 receptor and increased NADPH oxidase activity